Antioxidant activities and total phenolic content of the aqueous and methanol extracts of Mango seeds (mangifera indica) / Nor Azzua Iszham - Nor Azzua, Iszham (Faculty of Applied Sciences, 2009)
This study was carried out to calculate the antioxidant activity and to verify the total phenolic content of mango seeds. Methanol and water were used was solvent to extract the seeds’ chemical compound. Ferric thiocyanate, thiobarbituric acid and 1,1-diphenyl-2-picrylhydrazyl tests were done to measure the antioxidant activity and the phenolic contents of the sample was measured by using the total phenolic content test. The total phenolic content were plotted against the standard calibration curve of Gallic acid and the value shows that methanol extract (83,434 mg/g) contain higher phenolic content as compared to water extract (83,122 mg/g). Methanol extract also showed high scavenging activity at 96.21% and water extract only at 90.24% in the 1,1-diphenyl-2-picrylhydrazyl test. As for thiobarbituric acid and ferric thiocyanate tests, the results showed that the antioxidant activity of mango seeds is greater in thiobarbituric acid test, methanol extract at 95% and water extract at 94%, compared to in ferric thiocyanate test, methanol extract at 1.3% and water extract at 40.44%, which indicated that both water and methanol extract of crude compound has a larger number of peroxide in the secondary stage of lipid peroxidation than in the initial stage. For both methods showed that water extract has a greater antioxidant activity compared to methanol extract.